Detailed prenatal and postnatal MRI findings and clinical analysis of RAF1 in Noonan syndrome - Helenius Kjell; Parkkola Riitta; Arola Anita; Peltola Ville; Haanpää Maria K (Elsevier, 2022)
Noonan syndrome is a genetically heterogeneous developmental disorder, which usually includes findings such as short stature, facial dysmorphia, cardiac abnormalities and a varying degree of intellectual disability. We present a unique case of a rare variant of Noonan syndrome in a very preterm female infant born at 28 + 4 gestational weeks, with abnormal radiological findings visible at fetal magnetic resonance imaging (MRI) and evolution of the brain lesions during infancy.